Axial substitution and antibacterial activities of cobalt(III) complexes of an octamethyl substituted tetraaza macrocyclic ligand (Journal of Bangladesh Academy of Sciences, 2026)
Six-coordinate cobalt(III) complexes containing octamethyl-substituted tetraazamacrocyclic ligand Me8[14]diene have been synthesized and characterized. The trans-dichlorido diastereomeric complexes, trans-[CoLαCl2](ClO4) and trans-[CoLβCl2](ClO4), were obtained via aerial oxidation of the solution containing ligand and Co(II)-salt, with the addition of HCl & HClO4. Subsequently, the precursor diastereoisomer trans- [CoLαCl2](ClO4) underwent axial substitution reactions with NO3⁻, NO2⁻, SCN⁻, Br⁻, and I⁻ ions to afford a range of cobalt(III) trans- derivatives. CHN analysis, conductance analysis, infrared, proton, carbon-13 nuclear magnetic resonance, electronic spectroscopic methods, and magnetic susceptibility were used to characterize these complexes. Analytical results have proven the presence of a d⁶ low spin metal ion cobalt(III) in an octahedral environment, where the macrocycle occupies an equatorial plane while anions occupy an axial plane. Conductometric studies suggest the electrolytic properties of the complexes. The biological activities of the complexes in terms of their antibacterial properties were tested for selected Gram-positive and Gram-negative bacteria, showing that they have moderate-to-poor efficacy against these bacteria in comparison with a reference drug like ampicillin and increased effectiveness in comparison with the free ligand. This is very useful in explaining how cobalt(III) undergoes axial substitution under tetraazamacrocyclic conditions, which further goes to show how the presence of anion ligands affects their physicochemical and biological properties.J. Bangladesh Acad. Sci.50(2); 315–327: June 2026